Nuclear β-Catenin Accumulation Correlates with Poor Survival in Undifferentiated Nasopharyngeal Carcinoma: A Retrospective Cohort Study in an Endemic Region - Ayu Aksara; Awal Prasetyo; Devia Eka Listiana (HM Publisher, 2026)
Background: Nasopharyngeal carcinoma (NPC) is highly endemic in Indonesia, characterized by a prevalence of undifferentiated subtypes and late-stage presentation. While the Epstein-Barr virus (EBV) is a primary driver, the limitations of TNM staging in predicting individual outcomes necessitate the identification of molecular biomarkers. This study investigates the prognostic utility of aberrant Wnt/β-catenin signaling, specifically nuclear accumulation, in predicting overall survival (OS). Methods: A retrospective cohort study was conducted on 44 patients diagnosed with undifferentiated NPC at Dr. Kariadi General Hospital, Indonesia, between 2020 and 2024. Immunohistochemistry (IHC) for β-catenin was performed, with scoring specifically targeting nuclear and cytoplasmic reactivity (excluding physiological membranous staining) using the Allred system. Clinicopathological variables, including TNM staging (AJCC 8th edition), were analyzed. Survival analysis utilized Kaplan-Meier curves and multivariate Cox Proportional Hazards regression. Results: The cohort exhibited advanced disease, with 81.8% of patients presenting at Stage III or IV. Nuclear β-catenin overexpression (moderate-to-strong) was observed in 97.7% of cases. Strong nuclear expression was significantly associated with advanced T-stage (p=0.032) and distant metastasis (p=0.045). Kaplan-Meier analysis revealed a significant reduction in 5-year overall survival for the strong expression group (0%) compared to the weak/moderate group (p < 0.001). In multivariate analysis adjusted for age and TNM stage, strong β-catenin expression remained a significant predictor of mortality (Hazard Ratio: 2.15; 95% CI: 1.05–4.42; p=0.036), alongside Stage IV disease. Conclusion: Nuclear accumulation of β-catenin is a prevalent molecular event in Indonesian NPC and serves as a significant prognostic biomarker independent of tumor stage. These findings suggest potential utility for risk stratification and targeted Wnt-inhibitor therapies.